Resident evil. Extinction [videorecording (DVD)] - Mulcahy, Russell, 1953-; Jovovich, Milla; Fehr, Oded, 1970-; Larter, Ali, 1976- (Sony Pictures Home Entertainment, 2008)
Years after the Raccoon City disaster, Alice is on her own. She is aware that she has become a liability and could endanger those around her and she struggles to survive and bring down the Umbrella Corporation led by the sinister Albert Wesker and head researcher Dr. Isaacs. Meanwhile, traveling through the Nevada Desert and the ruins of Las Vegas, Carlos Olivera, L.J., and new survivors K-Mart, Claire Redfield, and Nurse Betty must fight to survive extinction against hordes of zombies, killer crows and a terrifying creatures created as a result of the deadly T-Virus that has already killed millions.